(untitled) - Latham-Koenig, Christina (Oxford, 2014)
The English File concept remains the same - fun, enjoyable lessons which get students talking through the right mix of language, motivation, and opportunity - but now the content and the components have been updated and improved for students and teachers.
Keywords: Anh ngữ,English language; Dạy và học,Nói tiếng nước ngoài,Study and teaching,Foreign speakers